2020
DOI: 10.1111/apt.15671
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: a clinical decision tool to identify patients who might benefit most from intensified dosing in the biological era—getting nearer? Authors' reply

Abstract: LINKED CONTENTThis article is linked to Dulai et al and Verstockt and Ferrante papers. To view these articles, visit https://doi.org/10.1111/apt.15609 and https://doi.org/10.1111/apt.15634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Lower Harvey-Bradshaw Index (HBI) baseline values, female sex and UST trough levels were predictors [29][30][31][32]. Dulai et al [33] created the UST clinical decision support tool (UST-CDST), which was derived from a post hoc analysis of UNITI trials. Using real-world data, the UST-CDST has demonstrated effectiveness in predicting clinical remission and relapse of UST in patients with moderate to severe CD [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lower Harvey-Bradshaw Index (HBI) baseline values, female sex and UST trough levels were predictors [29][30][31][32]. Dulai et al [33] created the UST clinical decision support tool (UST-CDST), which was derived from a post hoc analysis of UNITI trials. Using real-world data, the UST-CDST has demonstrated effectiveness in predicting clinical remission and relapse of UST in patients with moderate to severe CD [34].…”
Section: Discussionmentioning
confidence: 99%
“…10 Other tools have been developed for ustekinumab in Crohn's disease, 11 and recently, it has been demonstrated that the ustekinumab and vedolizumab tools for Crohn's disease are indeed drug specific and allow for discrimination of an individual patient for choosing between these agents. 12 The capacity to include patient specific data (smoking status, C-reactive protein results, etc. ), allows modeling to be tailored to the patient and therefore brings forward CER into a new era of personalization.…”
mentioning
confidence: 99%